1986-1987 ネン マクマードサウンド チイキ ノ コクサイ キョウドウ カンソク - 神沼, 克伊; カミヌマ, カツタダ; Kaminuma, Katsutada (1987)
P(論文) 日本の1986-1987年の国際共同観測は「マクマードサウンド地域の地球科学的研究」を継続した。神沼克伊(国立極地研究所), 三浦哲(東北大学理学部), 和田秀樹(静岡大学理学部)の3名が1986年11月中旬から1987年1月中旬まで, ニュージーランドのスコット基地に滞在し, 共同観測を実施した。主なテーマは1) CIROS (Cenozoic Investigation in the Western Ross Sea) 2) IMEEMS (International Mount Erebus Eruption Mechanism Study)の二つである。CIROSはロス海氷上での掘削プロジェクトで702mの掘削に成功し, 日本の分担したガス分析を和田が実施した。IMEEMSはエレバス山の噴火機構の研究で, 神沼と三浦が日本の分担課題を実施した。 Three Japanese scientists stayed at Scott Base to participate in two cooperative projects by Japan and New Zealand during the 1986-1987 Antarctic field season. They were K. KAMINUMA (National Institute of Polar Research), S. MIURA (Faculty of Science, Tohoku University) and H. WADA (Faculty of Science, Shizuoka University). They conducted the following two scientific research programs : 1) CIROS (Cenozoic Investigation in the Western Ross Sea) and 2) IMEEMS (International Mount Erebus Eruption Mechanism Study). WADA bore the responsibility of gas analysis at the CIROS drilling site, and carried out geochemical surveys in the Dry Valleys area after the drilling was finished. KAMINUMA and MIURA carried out the following items of IMEEMS : 1) seismic observation by means of the telemetry network, 2) temperature measurements in the summit crater, and 3) gravity measurements. departmental bulletin paper